Evaluation of Enzyme-Linked Immunosorbent Assays and a PCR Test for Detection of Shiga Toxins for Shiga Toxin-Producing Escherichia coli in Cattle Herds - Segura-Alvarez, Monserrat (American Society for Microbiology, 2003)
Antigen capture enzyme-linked immunosorbent assays (ELISAs) for the detection of Stx1 and/or Stx2 in cattle feces were validated in comparison to the Vero cell cytotoxicity neutralization test (as a “gold standard”) applied in the course of a monitoring program for Shiga toxin-producing Escherichia coli in German cattle herds as a prescreening test and compared to MK1/MK2 PCR as an alternative prescreening test.